(untitled) (Global Journal of Medical Research, 2023)
Aim and objective To predict preterm deliveries in symptomatic patients using a bedside kit for phosphorylated Insulin like Growth Factor Binding Protein-1 in cervical secretion It will enrich obstetricians in early identification preparedness and timely obstetricians interventions to reduce anticipated fetal complications in threatened preterm Materials and methods It was hospital based cross-sectional study including 78 pregnant women between 28 weeks to 37 weeks of gestation with threatened preterm labor Phosphorylated Insulin Like Growth Factor Binding Protein Test was done and data analysis was done using Student s t test Receiver operator characteristic curve and chi square test